Brimonidine Toxicity Secondary to Topical Use for an Ulcerated Hemangioma. Issue 4 (9th June 2016) - Gill, Kamalvir; Bayart, Cheryl; Desai, Ritu; Golden, Alex; Raimer, Patricia; Tamburro, Joan
Abstract: Combigan (Allergan, Irvine, CA) is an ophthalmic solution that combines 0.2% brimonidine, a selective α‐2 adrenergic agonist, with 0.5% timolol, a nonselective β‐adrenergic antagonist. It is approved for the reduction of intraocular pressure in patients with glaucoma or ocular hypertension. There have been recent reports of successful treatment of superficial infantile hemangiomas (IHs) using Combigan topically. We report the case of a 2‐month‐old girl who developed life‐threatening brimonidine toxicity requiring intubation and mechanical ventilation secondary to central nervous system depression and apnea after topical application to an ulcerated IH.